Analisa Heat Loss pada Pipa dari Demister Ke Turbin pada Pembangkit Listrik Tenaga Panas Bumi Lahendong Unit-2 - Teshalonikha Gabriel Iglesia Miranda Saburu; Satyano Mongan; Jefferson Polii (Jurnal FisTa : Fisika dan Terapannya, 2022)
Geothermal Power Plant in Lahendong is the largest power plant unit with environmentally friendly energy, with geothermal resources in North Sulawesi. At the Geothermal Power Plant in Lahendong unit-2, there are important components used to convert steam into electricity. These components include a demister, turbine, condenser, generator, cooling tower, injection well, and also a heat exchanger. One of the important pipes in the line of the Geothermal Power Plant is the pipe between the demister to the turbine. In the flow of steam in the unit-2 pipe from the demister to the turbine, it may experience heat loss during steam flow. The purpose of this study was to determine the amount of heat loss in the pipe from the demister to the turbine at Geothermal Power Plant Lahendong unit-2. This research uses the Steam Tabie application and Microsoft Excel. In this study, the results of the calculation of heat loss along the pipe from the demister to the turbine at the Lahendong Unit-2 Geothermal Power Plant amounted to 4465699 kJ/s